Classification of Disruptions Occurring At The Ferry Terminal in Poland - Daria CYBULSKA (Communications of International Proceedings, 2025)
The market for transport services faces the development of ferry shipping for both cargo and passengers. While performing the transport services, various disruptions may occur at the ferry terminals. Challenges related to the proper management of cargo or passenger handling processes at the ferry terminal result from the need for cooperation of shipowners, terminal managers or persons supervising ferry lines. These entities are responsible for making decisions and reacting immediately during any disruptions. The literature review carried out showed that issues related to the occurrence of disruptions at ferry terminals in Poland have been analysed to a limited extent. The objective of this article is to make an attempt to identify and classify the disruptions occurring at the ferry terminal in Poland. The article analyses ferry traffic in Poland and discusses an example of possible development of disruptive situations. Based on the literature review results and observations, the disruptions that may occur in the area of the ferry terminal were identified and classified. It was stated that in order to reduce the negative impact of disruptions, ferry terminals managers and shipowners should develop and implement specific procedures for different scenarios of undesirable events development. The results of the research may be of interest to ferry terminal managers, shipowners and ferry lines managers.
Keywords: ferry terminal; disruption; classification; ferry shipping.